Aspirin metabolism and efficacy in postoperative dental pain. - Seymour, R A (1984)
Aspirin 1200 mg was compared with placebo in a randomised, double-blind, crossover study in 15 patients with postoperative pain after removal of impacted lower third molars. Over a 5 h investigation period, patients reported significantly less pain (P less than 0.01) after treatment with aspirin, than after treatment with placebo. Peak concentrations of aspirin occurred at 15 min after dosage. Significant negative correlations were observed between plasma aspirin esterase activity and both AUC aspirin (r = -0.904, P less than 0.001) and AUC analgesia (r = -0.91, P less than 0.001). Similarly, a significant correlation was observed between AUC aspirin and AUC analgesia (r = 0.96, P less than 0.001). Evidence from this study would suggest that an individual's pain relief in postoperative dental pain is determined by the rate of aspirin hydrolysis to salicylate.